Comparison of physical & chemical properties of Angelus MTA and new endodontic restorative material - Golsa Salehimehr, Shokoufeh Nobahar, Seyed-Mostafa Hosseini-Zijoud, Somaye Yari (Journal of Applied Pharmaceutical Science, 2014)
In current study the Iranian New Endodontic Restorative Material (NERM) with Angelus MTA, has been compared in term of physical and chemical properties such as; PH, Compressive Strength, release of calcium ions, and final phase of each product and setting time. Five samples of each dental material were prepared based on ISO standards to survey the physical and chemical properties of NERM and Angelus MTA. Structural survey for both dental material revealed a similar crystal structure and no significant differences were observed in the microstructure of the NERM and Angelus MTA. Setting time in NERM and Angelus MTA samples was 25 and 17 minutes, respectively (P
Keywords: Angelus MTA, New Endodontic Restorative Material, physical properties, chemical properties.